Your voice : an inside view - McCoy, Scott Jeffrey (Inside View Press, 2012)
A multimedia exploration of voice science and pedagogy that focuses on the needs of the singer. Disc includes extensive use of audio, video, and high-resolution photographic examples to support the text.